Demographics and Clinical Presentation of Early-Stage Legg-Calvé-Perthes Disease: A Prospective, Multicenter, International Study. Issue 2 (15th January 2021) - Laine, Jennifer C.; Novotny, Susan A.; Tis, John E.; Sankar, Wudbhav N.; Martin, Benjamin D.; Kelly, Derek M.; Gilbert, Shawn R.; Shah, Hitesh; Joseph, Benjamin; Kim, Harry K. W.
Abstract : Background: Children with Legg-Calvé-Perthes disease (LCPD) are classically described as small, thin, high-energy children presenting with a painless limp. Epidemiologic studies have historically been retrospective and regional in nature. The purpose of this study was to determine the demographic and clinical features of children presenting in the early stages of LCPD in an international, multicenter cohort. Methods: Children (6 to 10 years) in the early stages of LCPD (modified Waldenström stage I to IIa) were enrolled in a prospective, multicenter study. Demographic and clinical data at presentation were analyzed. Body mass index percentiles were determined using country-specific growth charts for children in the United States and India, two countries with largest enrollment. Statistical analyses included t -tests and chi-square. Results: A total of 209 children (86% males; mean age 7.9 ± 1.2 years) from 25 centers (six countries) were included. Eight-four percent of children presented with pain with or without a limp. Average pain score at presentation was 3 ± 2 (range 0 to 9), and 63% of children (n = 105) used pain medications. Of these children 65% required medication more than once per week. Thirty percent of children missed school due to pain in the past month, and of those, 74% missed at least 1 day per week. Twenty-nine percent of children from the United States and 20% of children from India were overweight or obese. Nineteen percent reported household smoking. Discussion: This prospective study provides a new international multicenter representation of early LCPD. The frequency of pain and missed school highlights the substantial morbidity and potential social cost and burden for children and families. The prevalence of being overweight/obese in our LCPD cohort was comparable to rates within the pediatric cohort as a whole, and fewer children have a history of smoke exposure than in previous reports. Level of Evidence: Level II, prospective comparative study